(untitled) (International Journal of Food and Nutritional Sciences, 2020)
While the fundamental purpose of business was to generate wealth for society and was based on an economic structure, managing commercial operations of the enterprise with humanitarian expectations has long been ingrained in Indian culture. The business community has long subscribed to the sarva loka hitam philosophy. Adding a personal touch to business: CSR programs are becoming a crucial component of Indian banks’ daily operations. Numerous bank initiatives are intangible, but they are essential to the expansion of the economy overall, the improvement of corporate competitiveness, and the goodwill that underpins it, all of which contribute to the success of the country. Indian banks are essential to nation-building efforts, and their commitment to corporate social responsibility guarantees that they provide value to all of their endeavors.